Analysis of The Influence of Training Effectiveness and Employee Engagement on Employee Retention Through Organizational Commitment as an Intervening Variable - Yoseph Yunianto P. Pardede; Siti Safaria (Institut Manajemen Wiyata Indonesia, 2026)
This study aims to analyze the influence of Training Effectiveness and Employee Engagement on Employee Retention with Organizational Commitment as an intervening variable at PT Mitra Bisnis Madani (PT MBM), an affiliated company (PPU Perusahaan Partner Usaha) of PT Permodalan Nasional Madani (PNM). PNM is a non-bank financial institution in Indonesia that focuses on empowering micro, small, and medium enterprises (MSMEs), as well as cooperatives. PNM is a subsidiary of BRI and is part of the Ultra Micro Holding. Its main services include microfinance through programs such as PNM Mekaar (for underprivileged women) and PNM ULaMM. PT Mitra Bisnis Madani focuses on car and motorcycle rental activities to support PNM’s operations in empowering MSMEs and faces various challenges related to managing employee competencies and workloads effectively to achieve optimal performance. This study examines the relationship between Training Effectiveness and Employee Engagement on Employee Retention, with Organizational Commitment as an intervening variable, using the path analysis method. Data were collected through a survey using a questionnaire distributed to all employees of PT Mitra Bisnis Madani across Indonesia. The variables studied include Training Effectiveness, Employee Engagement, and Employee Retention, with Organizational Commitment as the intervening variable. This research provides strategic recommendations for PT Mitra Bisnis Madani in managing these factors to achieve organizational sustainability